Angioedema associated with thrombolysis for ischemic stroke: analysis of a case‐control study. (2nd August 2019) - Vigneron, C.; Lécluse, A.; Ronzière, T.; Bouillet, L.; Boccon‐Gibod, I.; Gayet, S.; Doche, E.; Smadja, D.; Di Legge, S.; Dumont, F.; Gaudron, M.; Ion, I.; et al.
Abstract: Background: Bradykinin‐mediated angioedema (AE) is a complication associated with thrombolysis for acute ischemic stroke. Risk factors are unknown and management is discussed. Objectives: To clarify risk factors associated with bradykinin‐mediated AE after thrombolysis for acute ischemic stroke. Methods: In a case‐control study conducted at a French reference centre for bradykinin angiœdema, patients with thrombolysis for acute ischemic stroke and a diagnosis of bradykinin‐mediated angiœdema, were compared to controls treated with thrombolysis treatment without angiœdema. Results: Fifty‐three thrombolysis‐related AE were matched to 106 control subjects. The sites of attacks following thrombolysis for ischemic stroke mainly included tongue (34/53, 64%) and lips (26/53, 49%). The upper airways were involved in 37 (70%) cases. Three patients required mechanical ventilation. Patients with bradykinin‐mediated angiœdema were more frequently women [33 (62%) vs. 44 (42%); P  = 0.01], had higher frequency of prior ischemic stroke [12 (23%) vs. 9 (8%); P  = 0.01], hypertension [46 (87%) vs. 70 (66%); P  = 0.005], were more frequently treated with angiotensin‐converting enzyme inhibitor [37 (70%) vs. 28 (26%); P  < 0.001] and were more frequently hospitalized in intensive care medicine [ICU; 11 (21%) vs. 5 (5%); P  = 0.004]. In multivariate analysis, factors associated with thrombolysis‐related AE were female sex [odds ratio (OR), 3.04; 95% confident interval (CI), 1.32–7.01; P  = 0.009] and treatment with angiotensin‐converting enzyme inhibitors [(OR), 6.08; 95% (CI), 2.17–17.07; P  < 0.001]. Conclusions: This case‐control study points out angiotensin‐converting enzyme inhibitors and female sex as risk factors of bradykinin AE associated with thrombolysis for ischemic stroke. Abstract :